(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This study develops a holistic and practice-oriented methodology for achieving inclusive economic growth through the long-term enhancement of export-import potential. In many emerging economies, foreign trade is not simply a channel for market expansion; it is a foundational mechanism that introduces new technologies, stimulates competitiveness, and strengthens macroeconomic resilience. Guided by both classical and modern trade theories, this research explores how diversification, industrial upgrading, trade facilitation, and institutional reforms interact to support sustainable development. Drawing on international experience and recent economic reforms undertaken in Uzbekistan, the paper identifies key structural and policy factors that determine the effectiveness of trade-led growth. The findings suggest that only a coordinated approach combining innovation, strong institutions, and evidence-based policy design can transform export-import potential into a stable source of inclusive economic growth.